Shall we help? We help! Poland in the global system of developmental cooperation (Economic and Political Thought, 2016)
For Poland, the OECD and EU accession meant that it would join theassistance programmes designed for international development cooperation.This activeness has raised controversies among the Polish society andpoliticians since the very beginning because Poland is to change from a beneficiarystate into a donor state. The Ministry of Foreign Affairs and theDevelopment Cooperation Department, which is in its structure, are mainlyresponsible for assistance for Poland. Since 2015, we are obliged to submit0.33% of the GDP to the EU budget but we do not fulfil the requirement.The resources we managed to gather are transferred to the so-called prioritycountries, i.e. Belarus, Georgia, Moldova and Ukraine as well as Ethiopia,Kenya, Myanmar, Palestine, Senegal and Tanzania.